THE ROLE MEDIATION OF WORK SATISFACTION AND PERCEIVED ORGANIZATION SUPPORT ON THE INFLUENCE OF COMPENSATION AND WORKLOAD IN EMPLOYEES TURNOVER INTENTION - Ali Mauludi AC; Nik Haryanti; Siti Marpuah (PT. Mawadaku Sukses Solusindo, 2024)
The purpose of the study is to analyze the influence of compensation and workload mediated by work satisfaction and perceived organizational support on employee turnover intention. This study used a survey which 400 employees. Data analysis used the partial least squares structural equation modeling (PLS-SEM) technique. The result of the study is compensation has a positive and significant influence on the turnover intention workload has a positive and significant influent on the turnover intention. Work satisfaction has a mediation effect on compensation in Turnover Intention. Work satisfaction has a mediation effect on workload in Turnover Intention. Perceived Organizational Support has a mediation effect on the influence of compensation on Turnover Intention. Perceived Organizational Support has a mediation effect on workload in Turnover Intention. Therefore, this study gives input to a firm to know turnover intention by increasing their compensation support through work satisfaction and perceived organizational support. Furthermore, a firm can keep their turnover intention at a low level and keep their opportunity to increase employees’ income.